ANALISIS PERSEPSI MASYARAKAT TERHADAP SARANA HIBURAN KARAOKE DI KOTA PEKANBARU - Irmawati Br. Simamora; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research on a the emergence of such entertainment karaoke in the city pekanbaru that provide services and facilities interesting .The problems emerging from the study is whether motivation visitors to karaoke in the city pekanbaru. This problem student got the quantitative approach by using statistical product service solution ( spss ) version 17.0. Sample in this research was visitors karaoke and the people in around the location karaoke as many as 97. This study was conducted in two karaoke namely karaoke centers in panam and jalan. nangka , reason writer chose a karaoke is because every day visitors in karaoke is very crowded , so writer interested to have a research in karaoke this. Data analysis technique used is product moment correlation ( ppm ) with the format likert scale .The analysis of test data using validity .Reliability test , correlation and test the hypothesis. Based on approach above , we found that the public perception positive on entertainment karaoke facilities , The more crowded visitors performs karaoke with correlation value 0.972 with a significance 0.000 with the provisions of value probability sig or 0.05 ≥ 0.000, So the hypothesis accepted the public perception is perception that positive on entertainment karaoke facilities.Keywords: perception , the community , motivation and karaoke